2016
DOI: 10.4103/1793-5482.145327
|View full text |Cite
|
Sign up to set email alerts
|

Primary aneurysmal bone cyst of the petrous temporal bone: A case report and review of literature

Abstract: Aneurysmal bone cyst (ABC) arising in the petrous portion of the temporal bone is a rare entity with only five such reported cases in the literature. We report the case of a 28-year-old man who presented with a tender swelling in the right preauricular region with right ear discharge and conductive hearing loss of 4 years' duration. Computed tomography and Magnetic Resonance imaging showed a destructive lesion in the right petrous bone with cavitation consistent with the diagnosis of ABC. Gross total resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The most common manifestations of temporal aneurysmal bone cysts are painless masses, 9,10 headache, 11,12 ear pain, 13 tinnitus, 12 hearing loss, 13,14 facial paralysis, 12,14 vertigo 13,15 and otorrhoea. 13 Our patient presented with facial palsy and hearing loss, accompanied by loss of vestibular function (based on vestibular-evoked myogenic potential testing results), all of which indicated that nerves running through the internal auditory canal were involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common manifestations of temporal aneurysmal bone cysts are painless masses, 9,10 headache, 11,12 ear pain, 13 tinnitus, 12 hearing loss, 13,14 facial paralysis, 12,14 vertigo 13,15 and otorrhoea. 13 Our patient presented with facial palsy and hearing loss, accompanied by loss of vestibular function (based on vestibular-evoked myogenic potential testing results), all of which indicated that nerves running through the internal auditory canal were involved.…”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestations of temporal aneurysmal bone cysts are painless masses, 9,10 headache, 11,12 ear pain, 13 tinnitus, 12 hearing loss, 13,14 facial paralysis, 12,14 vertigo 13,15 and otorrhoea. 13 Our patient presented with facial palsy and hearing loss, accompanied by loss of vestibular function (based on vestibular-evoked myogenic potential testing results), all of which indicated that nerves running through the internal auditory canal were involved. Based on the absence of vertigo and the pre-operative vestibular-evoked myogenic potential testing results, we presumed that the patient's vestibular nerve was completely damaged because of tumour compression of the inner auditory canal, and therefore vertigo could not have occurred post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Only 6 cases of ABC involving the petrous and/or mastoid portion of the temporal bone have been reported in the literature. 6 …”
Section: Discussionmentioning
confidence: 99%
“…19 In our review of temporal bone ABCs, we noted that the petrous portion of the temporal bone was the most commonly involved site and that ABCs rarely extended to more than 1 portion of the temporal bone. Three cases described ABC involvement of the petrous and squamous portions, 7,15,16 with no prior reports of concurrent involvement of the mastoid, petrous, and squamous portions.…”
Section: Discussionmentioning
confidence: 99%
“…This report is the ninth histologically confirmed case of ABC of the temporal squamosa in the English literature 7,[10][11][12][13][14][15][16] and the first report of ABC of any subtype involving the petrous, mastoid, and squamous portions of the temporal bone. This is also the first reported case of SVABC of the temporal bone.…”
Section: Introductionmentioning
confidence: 99%